Emergent transnational perspectives upon a folk cinema. Issue 1 (2nd January 2021) - Chambers, Jamie; Higbee, Will
ABSTRACT: This article seeks to inaugurate the study of a folk cinema through co-positioning a pair of historically and culturally disparate case studies from Scotland and Morocco in Utopian montage. In doing so we explore the shared concerns and solidarities which Play Me Something (Timothy Neat, Scotland, 1990) an independent, arthouse film set on the small Scottish island of Barra, may complexly have in common with Amussu (Nadir Bouhmouch, Morocco, 2020), a politically-charged documentary made collectively with the indigenous Imider community in southeast Morocco. We do so within an interdisciplinary theoretical framework drawing from aspects of political theory, cultural studies and social geography, and contemporary discussions of political populism. Ultimately, we reflect upon what such an act of montage – articulating the Utopian promise of the folk revival, albeit within the more sobering context of 2021 – may illuminate for emergent perspectives on a transnational folk cinema that may, complexly, serve as a form of globalism from below.